The Evolution of Legal Assistance - Danielyan, Gevorg (Bulletin of Yerevan University C: Jurisprudence, 2023)
The article reveals the evolution of the legal foundations of legal support in the countries that gained independence in the post-Soviet era, as well as its socio-political and ideological antecedents based onthe example of Armenia. Particularly, it is shown, that in the Soviet state legal system, the positions regarding the advocacy, at least as a part of the state structure, have not been completely overcomed, but are accompanied by new excuses. On the other hand, we discussed the problem that formation of an advocacy called to guarantee the right to a fair trial is obstacled by the so-called «state mentality». In particular, an advocade is perceived as a litigant who defends criminals by all means, therefore a state is not obliged to «excessively» cover the needs of free legal support. The article thoroughly discusses the prerequisites for the evolution of legal assistance/legal support, especially the factor of legal culture, clear positions are expressed relating the issues arising from the scientific and practical dimension, and for overcoming the existing problems, and a number of legislative recommendations are offered, reference was made in a form of predictions.